Antioxidant Capacity and Nutritional Value of Potato Tubers (Solanum tuberosum L.) as a Dependence of Growing Conditions and Long-Term Storage - Dorota Wichrowska (Agriculture, 2021)
The aim of the study was to assess the interactive effect of the use of bio-fertilizer and organic matter brought into the soil, as well as to limit the use of mineral fertilization on the content of bioactive compounds in potato tubers cultivar ‘Satina’. The test results show a positive effect of the applied bio-fertilizer in all tested variants of organic fertilization (straw, fodder pea, manure) on the level of the tested compounds. Comparing the content of crude protein in tubers from plots where half the dose of mineral fertilization was applied, the use of bio-fertilizer increased the content of this component, especially after using straw. After 6 months of storage, organic fertilization had no significant effect on the protein content, while significant differences were found in tubers fertilized with mineral, in favor of the full dose of NPK fertilizers. The storage time increased the content of tyrosine, leucine, lysine, alanine, glutamic acid, and total AA, and also methionine, aspartic acid, and asparagine, while the content of isoleucine and phenyl-alanine decreased. The highest content of total polyphenols was found in tubers where the plots were covered with pea application, a full dose of mineral fertilizer, and the use of bio-fertilizer. Unfortunately, after 6 months of storage, potato tubers from plots fertilized with peas, especially those fertilized with half the dose of mineral fertilization and without the use of biofertilizer, significantly lost the most total polyphenols. Similar relationships were obtained for the level of chlorogenic acid in tubers, which is significantly correlated with the content of polyphenols, but only organic fertilization in the form of peas significantly increased the concentration of chlorogenic acid. On the other hand, the highest post-harvest antioxidant activity was characteristic of tubers from plots fertilized with manure, with a full dose of mineral fertilization and biofertilizer. During the 6-month storage, there was a decrease in the antioxidant capacity, on average 12.4% for the objects. This may indicate the influence of polyphenolic compounds as well as other antioxidants on the assessed trait.